Refractory ascites after laparoscopic cholecystectomy: a case report - Xiaoyun Cheng; Jin Huang; Aiming Yang; Qiang Wang (BMC Surgery, 2022)
Abstract Background Laparoscopic cholecystectomy is a common surgical option for gallstone disease with minimal trauma and rapid recovery. Ascites is a relatively uncommon complication after laparoscopic cholecystectomy and is more frequently observed in patients with preoperative abnormal liver function. However, patients without underlying liver disease develop refractory ascites after laparoscopic cholecystectomy are rare. We report a case of massive ascites caused by lymphatic injury after laparoscopic cholecystectomy. Case presentation A 63-year-old woman complained of abdominal discomfort and distension at the twelfth day after a laparoscopic cholecystectomy for gallbladder stones. Subsequently, the patient developed spontaneous bacterial peritonitis and a decreased output of urine. Abdominal computed tomography (CT) identified abdominal effusion. The patient received abdominocentesis and the volume of slightly turbid yellow ascites averaged 1500–2000 ml per day. The results of laboratory analysis of ascitic fluid showed the following: serum-ascites albumin-gradient (SAAG), 11–12 g/L; albumin, 11–14 g/L; triglycerides, 0.91 mmol/L. After the diuretic therapy, repeated large-volume paracentesis with albumin supplementation, administration of antibiotics and renal vasodilating medications, the patient’s symptoms did not relieve. Lymphoscintigraphy found a small amount of radioactive filling in the abdominal cavity. The patient finally received surgery with detection and ligation of the lymphatic leak. The ascites disappeared and the patient recovered well. Conclusions For patients with atypical characteristics of chylous ascites, lymphoscintigraphy could help to localize and qualify the diagnosis. Surgical treatment could be considered when conservative treatment fails.